2014
DOI: 10.3168/jds.2013-7694
|View full text |Cite
|
Sign up to set email alerts
|

Economic basis for the Nordic Total Merit Index

Abstract: Within a group of cooperating countries, all breeding animals are judged according to the same criteria if a joint breeding goal is applied in these countries. This makes it easier for dairy farmers to compare national and foreign elite bulls and may lead to more selection across borders. However, a joint breeding goal is only an advantage if the countries share the same production environment. In this study, we investigated whether the development of a joint breeding goal for each of the major dairy cattle br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 4 publications
0
31
2
2
Order By: Relevance
“…Poor female fertility could cause considerable economic loss as a consequence of increased additional inseminations, veterinary treatments and involuntary culling. Nordic countries are well known for putting higher economic weights on female fertility traits in the selection index, and are also among the countries of highest genetic levels on fertility 2 . A recent investigation, however, suggested that genetic progresses for female fertility traits in Nordic countries were still unsatisfactory 3 , which might be because the traits have low heritability, unfavorable genetic correlations with milk yield traits and are measured late in life 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Poor female fertility could cause considerable economic loss as a consequence of increased additional inseminations, veterinary treatments and involuntary culling. Nordic countries are well known for putting higher economic weights on female fertility traits in the selection index, and are also among the countries of highest genetic levels on fertility 2 . A recent investigation, however, suggested that genetic progresses for female fertility traits in Nordic countries were still unsatisfactory 3 , which might be because the traits have low heritability, unfavorable genetic correlations with milk yield traits and are measured late in life 4 .…”
Section: Introductionmentioning
confidence: 99%
“…During the last decades, the focus on including longevity and functional traits (mainly fertility, health, and conformation) in dairy cattle breeding goals has increased throughout the world (Leitch, 1994;Miglior et al, 2005;Kargo et al, 2014). Longevity is a complex trait that is highly affected by production and functional traits as well as other factors such as herd management and the farmer's decisions (Berry et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The income from beef has been generally low for dairy farms in Finland and this has reduced motivation to improve beef quality traits of dairy herds (Hietala and Juga 2017). Therefore beef traits are not used for dairy cattle breeding schemes (Hietala and Juga 2017) and they are not included in the current Nordic Total Merit (NTM) index for NRC (Kargo et al 2014). However, Hietala and Juga (2017) concluded that in production systems similar to Finland, where the majority of produced beef originates from dairy herds and beef production fall below consumption, adding beef traits in the breeding program for dairy breeds could enable more sustainable and profitable milk and beef production.…”
Section: Resultsmentioning
confidence: 99%